Cognitive-Behavioral Therapy in Preventing Residivitism in Pedophilia: A Systematic Review - Merry P; Nurul Muslihah; Titin Andri Wihastuti (International Journal of Science and Society, 2020)
Pedophilia is a personality disorder of sexual behavior deviations that have such great sexual desire in children. The intervention has given actively determines the success in the prevention of pedophilic perpetrators, the guidance of imprisonment is necessary to change the behavior of sexual deviations on pedophilia perpetrators, so it is expected that the effective cognitive-behavioral therapy is given to change the negative mindset towards the positive because a positive mindset can influence one's emotional condition and behavior. Systematic review aims to review rehabilitation programs through a therapeutic approach that has been designed to prevent recidivism in pedophilic practitioners. A systematic review through journal review on Nursing therapy on Pedophilia perpetrators. The systematic review began by regularly identifying on several scientific articles that had been published from 2014 to 2019 in the international database of PubMed, ProQuest, Science Direct. Selection is done using the PRISMA flow diagram and criticized using JBI Tools. After that, 28 articles were considered relevant to be conducted in the analysis of the Sitematics review. In a systematic review, it showed that cognitive therapy is a very effective therapy administered by pedophilia inmates to prevent recidivism. Rehabilitation with the therapeutic approach of an active cognitive behavior is given to pedophilia inmates in preventing recidivism so that the application development is needed to avoid sexual violence in children.